Using group sizes to optimise archery equipment - Park, J. L. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2023)
One method used by archers and coaches to optimise archery equipment is to measure the size of arrow groups on the target prior to and following an adjustment. The group sizes are then used to determine if an equipment change assisted or detracted from the archer`s performance. A model based on a Monte Carlo method and group size measurements from seven elite archers were used to test the validity of this process. The results showed that this method was neither an effective method nor useful process because the probability of false positives or false negatives was too great. A better approach to optimise archery equipment is to monitor the archer`s skill level or average score over an extended time following any change.